AKTIVITAS ANTIOKSIDAN DAN SKRINNING FITOKIMIA EKSTRAK ETANOL DAUN SINTRONG (Crassocephalum crepidioides (Benth) S. Moore) - indah trilestari; Panji Ratih Suci; Erna Fitriany (Akademi Farmasi Mitra Sehat Mandiri Sidoarjo, 2023)
Antioxidants is an important role in the body's defense against disease, because antioxidant compounds are able to prevent the bad influence caused by free radicals. Sintrong leaves (Crassocephalum crepidioides (Benth) S. Moore) has a compound of saponins, tannins, alkaloids and flavonoids known to be used as antioxidants. The purpose of the study to determine the activity of antioxidant and IC50 values as well as compounds contained there in and compared with Vitamin C as a positive control of antioxidant activity of sintrong leaves (Crassocephalum crepidioides (Benth) S. Moore). The research method uses DPPH attenuation method and then calculated by spectrophotometry to determine the antioxidant content. The results showed that ethanol extract of sintrong leaves has antioxidant activity that can ward off free radicals with IC50 value of 52.49 mg / ml. Conclusion there is antioxidant activity in sintrong leaf extract (Crassocephalum crepidioides (Benth) S. Moore) with IC50 value of 52.49 mg / ml (strong) but the antioxidant activity obtained greater positive control than the extract. This data is supported by the Independent T-Test the value of the thitung > ttabel, which means that there are differences in the antiokxidant activity of sintrong leaves and vitamin C. Keywords: Sintrong leaf, Free Radicals, Antioxidants, IC50.